Reading and editing the Pleurodeles waltl genome reveals novel features of tetrapod regeneration - Ahmed Elewa (Nature Portfolio, 2017)
The Iberian ribbed newt Pleurodeles waltl has a wide spectrum of regeneration abilities. Here, Elewa et al. sequence its ~20 Gb genome and transcriptome to investigate the molecular features underlying its regenerative capacities.